Pelaksanaan Kawin Paksa sebagai Tuntutan Adat dalam Perspektif Hukum Positif dan Hak Asasi Manusia - Nabila Maharani (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Forced marriages are often a hotly debated issue among the public because they are considered to have violated the rules that have been legalized in the laws enacted by the government. However, this is inversely proportional to the perception of ordinary people in some regions in Indonesia who view forced marriage as something that must be done to fulfill the customs that have been followed for generations. Therefore, there are differences of opinion and views between positive law and customary law regarding forced marriage. According to positive law, forced marriages due to customary demands are considered to have violated human rights. With this in mind, the researcher is interested in conducting an assessment of the implementation of forced marriages that often occur in Indonesia by using the library research method by examining the literature related to the topic of discussion.